To solve the quadratic equation \(x^2 + 8x = 9\) by completing the square, follow these steps:
-
Move the constant to the other side: \[ x^2 + 8x - 9 = 0 \] Now, we isolate the quadratic and linear terms: \[ x^2 + 8x = 9 \]
-
Complete the square: Take the coefficient of \(x\) (which is 8), divide it by 2, and square it: \[ \left(\frac{8}{2}\right)^2 = 4^2 = 16 \]
-
Add and subtract this square to the left side of the equation: \[ x^2 + 8x + 16 - 16 = 9 \] This can be rewritten as: \[ (x + 4)^2 - 16 = 9 \]
-
Move the subtracted square back to the right: \[ (x + 4)^2 = 9 + 16 \] \[ (x + 4)^2 = 25 \]
-
Take the square root of both sides: \[ x + 4 = \pm 5 \]
-
Solve for \(x\):
- For the positive square root: \[ x + 4 = 5 \quad \Rightarrow \quad x = 5 - 4 \quad \Rightarrow \quad x = 1 \]
- For the negative square root: \[ x + 4 = -5 \quad \Rightarrow \quad x = -5 - 4 \quad \Rightarrow \quad x = -9 \]
Thus, the two values that solve the equation \(x^2 + 8x = 9\) are: \[ x = 1 \quad \text{and} \quad x = -9 \]